2009
DOI: 10.4103/0250-474x.59551
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial evaluation of 5-iodopyrimidine analogs

Abstract: 4-Substituted-5-iodo-2-benzylthiopyrimidines were prepared efficiently in three steps. 2-Benzylthiopyrimidine on iodination in presence of base gave 5-iodo-2-benzylthiopyrimidine (1), which on chlorination with excess of POCl3 furnished 4-chloro-5-iodo-2-benzylthiopyrimidine (2). Reaction of 2 with substituted aromatic amines, 2-aminopyridine and hydrazine hydrate yielded 4-amino-5-iodo-2-benzylthiopyrimidines 3(a-e), (3f) and (3g) respectively. Further, 4-hydrazino-5-iodo-2-benzylthiopyrimidine on condensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The benzimidazole scaffold is a useful structural motif for displaying chemical functionality in biologically active molecules. Some of its derivatives have potent biological activities as antitumor [4], anti-HIV [5], anti-Parkinson [6], and antimicrobial [7] agents. At the same time, because of the coordination chemistry of azoles acting as ligands in transition metal compounds, the chelating ligands incorporating benzimidazole groups have been extensively studied in the context of modeling biological systems in recent years [8].…”
Section: Introductionmentioning
confidence: 99%
“…The benzimidazole scaffold is a useful structural motif for displaying chemical functionality in biologically active molecules. Some of its derivatives have potent biological activities as antitumor [4], anti-HIV [5], anti-Parkinson [6], and antimicrobial [7] agents. At the same time, because of the coordination chemistry of azoles acting as ligands in transition metal compounds, the chelating ligands incorporating benzimidazole groups have been extensively studied in the context of modeling biological systems in recent years [8].…”
Section: Introductionmentioning
confidence: 99%
“…The benzimidazols are useful intermediates/subunit for the development of pharmaceutically important molecules with biological interest. From a literature survey for the benzimidazols system, it is seen that many workers have found applications in diverse therapeutic areas including anticancer, antiparkinsonian, antihistaminic, and fungicides . The optimization of benzimidazole derivatives based on their structures has resulted in various potent drugs that are now being currently practiced in the market, such as Albendazole, Omeprazole, and Mebendazole.…”
Section: Introductionmentioning
confidence: 99%
“…From a literature survey for the benzimidazols system, it is seen that many workers have found applications in diverse therapeutic areas including anticancer, [4] antiparkinsonian, [5] antihistaminic, [6] and fungicides. [7] The optimization of benzimidazole derivatives based on their structures has resulted in various potent drugs that are now being currently practiced in the market, such as Albendazole, Omeprazole, and Mebendazole. Herein, we report the structure-based design, synthesis, and biological evaluation of benzimidazole-based inhibitors targeting the identified active sites of available crystal structure of MAO-A complex.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds possess versatile type of biological activities; some of these are well known for their anticancer [1][2] , antitubercular 3 , antibacterial 4 , antifungal 5 , anti-HIV 6 , anthelmintic 7 , anti-inflammatory 8 and antihypertensive activities 9 . Piperazines are found to be antimicrobial agents [10][11] . Structure activity relationship studies of quinazolinone ring system revealed in various literatures [12][13][14] suggest position 2, 6 and 8 are very much important for structure activity studies and position 3 should be attached to different heterocyclic rings for better chemotherapeutic activity.…”
Section: Introductionmentioning
confidence: 99%